2007
DOI: 10.1021/om700744b
|View full text |Cite
|
Sign up to set email alerts
|

Asymmetric Hydroformylation of Olefins with Rh Catalysts Modified with Chiral Phosphine−Phosphite Ligands

Abstract: Rhodium complexes stabilized by modularly designed chiral phosphine−phosphite ligands (P−OP) have been tested in the asymmetric hydroformylation of styrene, vinyl naphthalenes, and allyl cyanide. Based on single-crystal X-ray diffraction analysis and NMR studies, restricted aryl rotation has been found to characterize ligands 1e and 1f. The outcome of the rhodium-catalyzed hydroformylation reactions is highly dependent on the nature of the two coordinating functions of the phosphine−phosphite and of the ligand… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
33
0

Year Published

2010
2010
2022
2022

Publication Types

Select...
6
2
1

Relationship

2
7

Authors

Journals

citations
Cited by 63 publications
(35 citation statements)
references
References 44 publications
2
33
0
Order By: Relevance
“…Complexation of MOP with [Rh 2 Cl 2 (CO) 4 ] resulted in multiple species again being observed in the 31 (It is noteworthy that on a separate run of this complex, the broad peak at 47e48 ppm was observed).…”
Section: [Rh 2 CL 2 (Co) 4 ] In Cdclmentioning
confidence: 99%
See 1 more Smart Citation
“…Complexation of MOP with [Rh 2 Cl 2 (CO) 4 ] resulted in multiple species again being observed in the 31 (It is noteworthy that on a separate run of this complex, the broad peak at 47e48 ppm was observed).…”
Section: [Rh 2 CL 2 (Co) 4 ] In Cdclmentioning
confidence: 99%
“…The few cases where such hybrid ligands were studied have proved inconclusive. Thus, for example, in the case of asymmetric hydroformylation, Pizzano and co-workers found that their PeOP ligands which combined both axial and P-stereogenicity were less selective than their ligands without P-stereogenicity, suggesting that the chiralities were not co-operative [4,5].Conversely, Buchwald and co-workers have reported significantly improved ees when their P-stereogenic binaphthyl substituted monophosphines were tested in palladium catalysed asymmetric vinylation and arylation reactions [6,7]. Previously our group have reported the novel synthesis of P-stereogenic MOP analogues ( Fig.…”
Section: Introductionmentioning
confidence: 99%
“…Thus, M–P distances are typically longer for phosphines. For instance, for Pd(Cl) 2 (P‐OP) complexes, distances between 2.227 and 2.272 Å have been reported for the phosphine group (Table , entries 1–5), while the corresponding distances for the phosphite fragment are in the range between 2.187 and 2.214 Å 31–33. This trend is also observed in the case of [Rh(diolefin)(P‐OP)]BF 4 complexes (Table , entries 8–14), with ranges of 2.265–2.410 and 2.182–2.220 Å for the phosphine and phosphite fragments, respectively 34–38.…”
Section: Features Of P‐op Ligandsmentioning
confidence: 56%
“…This catalytic system provided Scheme 32 Rh-catalyzed asymmetric hydroformylation with the polystyrene supported ligand (R,S)-BINAPHOS (72) good conversions (up to 83%), excellent regioselectivities (up to 90%), and ees up to 93% (Scheme 31).…”
Section: Scaffolding Ligandsmentioning
confidence: 99%